Optimal microgrid formation to improve the resilience of power system withstanding the storm - Widiputra, Victor; Oh, Seongmun; Jung, Jaesung (IEEE Region 10 Humanitarian Technology Conference, R10-HTC, 2019)
The resilience index shows the performance of the power system to anticipate, absorb, recover, and adapt under major natural disaster. To increase the resilience index, the damage and its duration must be minimized. The distributed energy resource (DER) can improve the resilience index by forming a microgrid when the system is damaged. This paper proposes an algorithm to identify the optimal microgrid formation to improve the resilience index of the system. First, it finds the islanded buses in the power system by converting the system into its bus injection to bus current (BIBC) matrix. Then, the algorithm forms a microgrid by installing the DER in the islanded buses to improve the resilience index. To verify the algorithm, simulations are performed to obtain the resilience index under four storms that have happened in the past. The results show that the optimal microgrid formation can improve the system resilience to storms.
Keywords: Bus currents; Distributed energy resource; Major natural disasters; Micro grid; Resilience index; System resiliences; Distributed Energy Resource (DER); Grid Resilience; Major Natural Disaster; Microgrid; Optimum Placement